DIGITALISASI KEARSIPAN DALAM MENUNJANG PELAYANAN INFORMASI PADA UNIT TATA USAHA DI SMP NEGERI 3 SIABU - Azizah Rahmadani; Kasman Kasman; Afridah Afridah (STKIP Pesisir Selatan, 2026)
This research is motivated by the importance of implementing digitalization of archiving which is a transformation in the archiving system from conventional to digital form in order to increase the effectiveness, efficiency, and quality of information services in the school environment. The purpose of this study is to find out (1). how the digitalization of archiving is managed at SMP Negeri 3 Siabu (2). the impact of the implementation of digitalization of archiving in improving the quality of information service management at SMP Negeri 3 Siabu (3). inhibiting and supporting factors of digitalization of archiving in the administration of SMP Negeri 3 Siabu. The results of the study show that (1). the management of digitalization of archiving at SMP Negeri 3 Siabu has implemented digitalization of archiving quite well because the average TU has mastered IT, for example, such as monthly reports, division of teacher work tasks, incoming and outgoing letters, new student registration, RPP, report card grades, and online attendance using digital archives such as mobile applications (cloud storage) and dropbox. Student achievements, and promotion of school extracurricular activities are archived using Facebook and Instagram applications. BOS reports, teacher and education staff attendance reports, Dapodik data, appointment decrees, teaching assignment decrees, retirement decrees, and the implementation of UKKJ JF teachers have used digital archiving with the Google Drive and OneDrive applications.